Response Surface Optimization of Electro-Spun Polyvinyl Alcohol Nano-Fiber Membrane Process Parameters and its Characterization - Gebru, Kibrom Alebel; Das, Chandan (Journal of Membrane and Separation Technology, 2023)
An empirical exploration into the effects of time duration, voltage supply, concentration and flow rate on the membrane average fiber diameter and surface pore size distribution were done using response surface methodology (RSM) based on central compact design (CCD). The average fiber diameter and average surface pore diameter of the membrane (i.e. 110 nm and 130 nm, respectively) were obtained at optimum input parameters of 45 min, 10 wt. %, 12 kV and 1.0 mL/h for time duration, concentration, voltage supply, and flow rate, respectively. The optimization study shows that the predicted versus actual values of both membrane fiber diameter and surface pore diameter are at R2 = 0.96. In addition, the effect of glutaraldehyde on membrane crosslinking was also assessed for further studies. The results from FESEM images of the fabricated PVA nanofiber membranes using the optimized parameters revealed that the membranes showed smooth morphological structures without formation of beads. The thermo gravimetric analysis (TGA) results displayed an improvement in thermal stability after membrane crosslinking. From this study we have observed that the membrane average fiber diameter and surface pore diameter can be controlled by varying the electro-spinning parameters and can be utilized for wastewater treatment application.